Surgical Restoration of Antero-Apical Left Ventricular Aneurysms: Cardiac Computed Tomography for Therapy Planning - Solowjowa, Natalia; Nemchyna, Olena; Hrytsyna, Yuriy; Meyer, Alexander; Hennig, Felix; Falk, Volkmar; Knosalla, Christoph (Frontiers in Cardiovascular Medicine, 2022)
Background: Surgical ventricular restoration (SVR) leads to functional improvement by volume reduction and restoration of left ventricular (LV) geometry. Our purpose was to refine the planning for SVR using cardiac computed tomography (CCT). Methods: The possibility to anticipate the postoperative residual LV volume was assessed using CCT in 205 patients undergoing SVR combined with coronary artery bypass grafting (77%), mitral valve repair/replacement (19%) and LV thrombectomy (19%). The potential of CCT to guide the procedure was evaluated. Additionally, the predictive value of CCT characteristics on survival was addressed. Results: 30-day, one-year and five-year survival was 92.6%, 82.7% and 72.1%, respectively, with a marked reduction of NYHA class III-IV quota after surgery (95.1% vs. 20.5% in the follow-up). Both pre- and postoperative LV end-systolic volume index (LVESVI) were predictive of all defined endpoints according to the following tertiles: preoperative: <74 ml/m², 74–114 ml/m² and >114 ml/m²; postoperative: <58 ml/m², 58–82 ml/m² and >82 ml/m². On average, a 50 ml/m² increase of preoperative LVESVI was associated with a 35% higher hazard of death (p=0.043). Aneurysms limited to seven antero-apical segments (7, 8, 13, 14, 15, 16, 17) were associated with a lower death risk (n=60, HR 0.52, CI 0.28–0.96, p=0.038). LVESVI predicted by CCT was found to correlate significantly with effectively achieved LVESVI (r=0.87 and r=0.88, respectively, p<0.0001). Conclusions: CCT-guided SVR can be performed with good mid-term survival and significant improvement in HF severity. CCT-based assessment of achievable postoperative LV volume helps estimate the probability of therapeutic success in individual patients.